Polymer emulsifier for cold-mixed and cold-laid emulsified asphalt concrete and preparation method thereof

By using terpolymer emulsifiers generated by polymerization of acrylamide, N-vinylpyrrolidone and N-vinylimidazole, the problem that cold-mixed emulsified asphalt concrete is difficult to use as a surface layer due to low viscosity and low solid content of emulsified asphalt, it has achieved emulsified asphalt with high viscosity and good stability, and expanded its application range.

CN119875005AActive Publication Date: 2025-04-25CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY +3
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411847248.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing cold-mixed emulsified asphalt concrete is difficult to use as a surface layer due to the low viscosity and low solid content of emulsified asphalt, which limits its application scope.

Method used

The ternary polymer emulsifier produced by polymerization of acrylamide, N-vinylpyrrolidone and N-vinylimidazole is prepared by adjusting the molar ratio of the monomer and the preparation method.

Benefits of technology

The viscosity and solid content of emulsified asphalt is improved, making it easier to operate during construction, has a wider range of application, and significantly improves storage stability and construction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875005A_ABST
    Figure CN119875005A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of road materials, in particular to a polymer emulsifier for cold-mixed and cold-laid emulsified asphalt concrete.The polymer emulsifier is a ternary polymer generated by polymerization of acrylamide (AM), N-vinyl pyrrolidone (NVP) and N-vinyl imidazole (NVI), and the molecular weight of the polymer emulsifier is 3000-10000; wherein the molar ratio of the AM monomer to the NVP monomer to the NVI monomer is (5-2): 3: (2-5). The ternary polymer emulsifier can be used for high-viscosity and high-solid-content emulsified asphalt, so that the emulsified asphalt still has good storage stability under the condition of high solid content, the application range of the emulsified asphalt can be widened, and the problems that the modified emulsified asphalt prepared by the prior art is difficult to consider high solid content, high viscosity and good storage stability; the surface layer is difficult to use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road materials, and in particular to a polymer emulsifier for cold-mix cold-paved emulsified asphalt concrete and a preparation method thereof. Background Art

[0002] Asphalt is a viscous or semi-solid petroleum product widely used in road construction, waterproof materials and other fields. Emulsified asphalt is a liquid asphalt product made by mixing asphalt particles with water and adding an appropriate amount of emulsifier through mechanical stirring. It is easy to construct and environmentally friendly. The essence of emulsified asphalt is a mixture of asphalt particles stably dispersed in water containing emulsifiers. Cold-mix emulsified asphalt concrete refers to a mixture made by mixing emulsified asphalt with aggregates (such as crushed stone, sand, etc.) and fillers (such as mineral powder) when necessary in a certain proportion under normal temperature conditions. The advantage of cold-mix emulsified asphalt concrete is that it can achieve good construction performance without heating.

[0003] Using cold-mix emulsified asphalt concrete instead of hot-mix asphalt concrete can significantly reduce carbon emissions, and the construction process is environmentally friendly and less affected by weather factors. However, due to the low viscosity and low solid content of the original asphalt used to prepare emulsified asphalt, it can usually only be used as a functional layer material in occasions such as penetration layer, adhesive layer, and slurry seal, and is difficult to use as a cold-mix cold-laid asphalt concrete surface layer. It can be seen that the low viscosity and low solid content of the current emulsified asphalt are the main problems that limit the application scope of cold-mix emulsified asphalt concrete. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a polymer emulsifier for cold-mix cold-laid emulsified asphalt concrete. The polymer emulsifier can be used to prepare high-viscosity and high-solid emulsified asphalt, and the emulsified asphalt is further made into cold-mix emulsified asphalt concrete, thereby solving the technical problem that the currently prepared cold-mix emulsified asphalt concrete is generally difficult to use as a surface layer due to the low viscosity and low solid content of the emulsified asphalt.

[0006] (II) Technical solution

[0007] In the first aspect, the present invention provides a polymer emulsifier for cold mix and cold laid emulsified asphalt concrete, wherein the polymer emulsifier is a terpolymer generated by polymerization of acrylamide AM, N-vinyl pyrrolidone NVP and N-vinyl imidazole NVI, and the molecular weight thereof is 3000-10000; wherein the molar ratio of the three monomers AM, NVP and NVI is 5-2:3:2-5; preferably, the molar ratio of the three monomers AM, NVP and NVI is 5:3:2.

[0008] In a second aspect, the present invention provides a method for preparing a polymer emulsifier for cold mix cold paving emulsified asphalt concrete, comprising the following steps:

[0009] S1, dispersing acrylamide monomer AM, N-vinyl pyrrolidone monomer NVP and N-vinyl imidazole monomer NVI in water to obtain a mixed solution;

[0010] S2, treating the mixed solution to remove or reduce dissolved oxygen in the mixed solution;

[0011] S3. Under the protection of inert gas, add a water-soluble initiator to the mixed solution, control the reaction temperature to ≤53°C to carry out polymerization reaction, and keep stirring during the polymerization process;

[0012] S4. After the reaction is completed, acetone is added to the reaction system for precipitation, the precipitate is washed, and dried in a vacuum drying oven to obtain an AM-VP-VI ternary polymer emulsifier.

[0013] According to a preferred embodiment of the present invention, in S1, the molar ratio of the three monomers AM, NVP and NVI is 5-2:3:2-5; preferably, the molar ratio of the three monomers AM, NVP and NVI is 5:3:2. When AM takes the upper limit of the ratio, NVI takes the lower limit of the ratio; conversely, when AM takes the lower limit of the ratio, NVI takes the upper limit of the ratio.

[0014] In the AM-VP-VI ternary polymer, the monomer AM has good water solubility, and the increase in its proportion can improve the hydrophilicity of the polymer chain, solubility or dispersibility in water, and increase water absorption capacity and viscosity; the monomer NVP has higher hydrophilicity, and the increase in its proportion can significantly enhance the water solubility of the polymer and its compatibility with polar substances; NVP can enhance the film-forming ability of the copolymer and has a certain biodegradation potential. NVI carries a cationic charge and shows a certain hydrophilicity in water, but at the same time, due to the presence of the ring structure, it also gives the polymer a certain hydrophobic property; NVI can introduce positive charges, and the increase in its proportion can enhance the interaction between the copolymer and the negatively charged surface, and may also increase the antibacterial properties of the material. By changing the ratio of the three monomers, the hydrophilicity / hydrophobicity of the copolymer can be controlled. An appropriate proportion of NVI can obtain a polymer with a certain hydrophobicity but good water dispersibility.

[0015] The AM-VP-VI ternary polymer cationic emulsifier provided by the present invention has a molecular weight of 3000-10000. On the one hand, its long chain structure is intertwined with asphalt molecules and anchored in asphalt particles. On the other hand, by introducing hydrophilic groups such as amide groups, imidazole five-membered heterocyclic rings and pyrrolidone groups into the molecular structure, the interaction between these molecules and water can be enhanced, and the interfacial tension between asphalt and water can be reduced through the steric hindrance effect, thereby improving the storage stability of the emulsified asphalt system.

[0016] According to a preferred embodiment of the present invention, in S1, the total molar concentration of the three monomers in the mixed solution is 1.2-1.8 mol / L, preferably 1.5 mol / L.

[0017] According to a preferred embodiment of the present invention, in S2, nitrogen is introduced into the mixed solution to remove or reduce dissolved oxygen in the mixed solution; specifically, nitrogen is continuously introduced into the mixed solution for 30-50 minutes.

[0018] According to a preferred embodiment of the present invention, in S3, the water-soluble initiator is azobisisobutylamidine hydrochloride, which has good water solubility and can efficiently initiate polymerization reactions in aqueous solutions; efficient initiation: compared with general azo initiators, AAPH has a higher initiation efficiency, can generate polymers with relatively high molecular weight and good water solubility, and less residual substances. Mild decomposition conditions: AAPH can be decomposed at a relatively low temperature to produce highly linear and high molecular weight polymers; suitable for polymerization reactions under low temperature conditions. After decomposition, AAPH releases two cationic groups and nitrogen, does not contain toxic cyano groups, and the decomposition products are non-toxic, safer and more environmentally friendly. Under light conditions, especially under ultraviolet irradiation, AAPH can efficiently initiate polymerization reactions.

[0019] According to a preferred embodiment of the present invention, in S3, azobisisobutylamidine hydrochloride is added in a low-concentration solution in a uniform flow during the polymerization reaction, and the reaction temperature is controlled at 50°C; preferably, the solution concentration of azobisisobutylamidine hydrochloride is 0.05-0.06mol / L, and the total amount of azobisisobutylamidine hydrochloride is 1 / 6-1 / 8 of the total molar ratio of the reaction monomers; in S3, the stirring speed during the polymerization is 180rpm-220rpm; the reaction time is 7.5-8.5h. Azobisisobutylamidine hydrochloride can also be replaced by an equimolar amount of azobiscyanovaleric acid ACVA, ammonium persulfate APS or potassium persulfate KPS; ACVA, APS and KPS have good water solubility and can be used to replace azobisisobutylamidine hydrochloride. Azobisisobutyronitrile AIBN or azobisisovaleronitrile AIVN has poor water solubility and contains toxic cyano groups, so it is not safe and environmentally friendly.

[0020] According to a preferred embodiment of the present invention, in S4, after the reaction is completed, 1.5-3 times the volume of acetone of the reaction system is added to the reaction system, stirred, allowed to stand, the precipitate is separated, and the precipitate is washed with ethanol 2-3 times; dried in a vacuum drying oven at 50°C for 24h to obtain an AM-VP-VI ternary polymer emulsifier.

[0021] In a third aspect, the present invention provides an emulsified asphalt comprising 70-75% of a modified base asphalt, 0.5-1.2% of the AM-VP-VI ternary polymer emulsifier described in claim 8, 0.1-0.5% of a solid nano-powder stabilizer, 0.1-1% of an auxiliary agent and the remainder of water; the auxiliary agent comprises a pH regulator, which adjusts the pH of the emulsified asphalt to 2-3; the solid nano-powder stabilizer is a nano-scale anhydrous calcium chloride powder; the modified base asphalt is a base asphalt co-modified by SBS and SBR.

[0022] Wherein, the matrix asphalt is 70# matrix asphalt, which can be one of SK-90, Zhonghai-90 and Jingbo-90. Preferably, the additive may include other additives in addition to the pH adjuster, such as a thickener, an antioxidant, a rust inhibitor and a preservative, and other additives may be added as needed. The pH adjuster maintains the emulsified asphalt at a lower pH, such as a pH of 2-3, and the pH adjuster is hydrochloric acid. Preferably, the matrix asphalt is road petroleum asphalt.

[0023] SBS (Styrene-Butadiene-Styrene Block Copolymer) and SBR (Styrene Butadiene Rubber) co-modified matrix asphalt is used to improve the performance of the matrix asphalt. The SBS and SBR co-modified matrix asphalt can be modified according to the existing technology. For example: the matrix asphalt can be melted under heating conditions, and then the pre-weighed SBS and SBR are dispersed in the matrix asphalt, and processed for 5-10 minutes using a shearing machine (such as a speed of 10000-12000rpm). According to experiments, SBS accounts for 3-6% of the mass of the matrix asphalt, and SBR accounts for 2-4% of the mass of the matrix asphalt; when the SBS content is 5% and the SBR rubber powder content is 4%, the prepared modified matrix asphalt can obtain good comprehensive performance.

[0024] SBS forms an elastic network structure, which allows asphalt to maintain a certain flexibility at low temperatures and is not easy to flow at high temperatures; SBR increases the viscosity and cohesive strength of asphalt and improves its deformation resistance. SBS provides better high and low temperature performance, while SBR helps to enhance the durability and adhesion of asphalt. SBS gives asphalt good low-temperature ductility and high-temperature stability, reduces temperature sensitivity, improves the durability of the road surface under extreme weather conditions, increases the elasticity and recovery ability of asphalt, and reduces the risk of cracks caused by repeated vehicle loads. The addition of SBR enhances the adhesion of asphalt to aggregates, while improving waterproof performance and reducing the possibility of water damage. The appropriate proportion of SBS and SBR can make the modified asphalt have better fluidity and pumpability, which is convenient for construction operations.

[0025] Preferably, the particle size of the nano-scale anhydrous calcium chloride powder is 1-100nm, preferably 20-50nm; preferably, the nano-scale anhydrous calcium chloride powder is pre-surface-modified (impregnated) with hexadecyltrimethoxysilane (CTMS) to improve its dispersibility in water. Solid nanoparticles spontaneously adsorb on the oil-water interface to form a protective film to prevent agglomeration between droplets, thereby achieving long-term stability of the emulsion. Unlike emulsified asphalt stabilized with surfactants, because nano-inorganic powders are not easy to desorb from the interface (irreversible adsorption of solid particles), this protective film is more stable than the film formed by traditional surfactants. Emulsified asphalt has high thermodynamic stability and can remain stable even under extreme conditions (such as high temperature and high salt concentration).

[0026] Among them, the AM-VP-VI ternary polymer emulsifier prepared by the present invention, on the one hand, plays the role of emulsifying and dispersing asphalt, and on the other hand, can modify the emulsified asphalt, improve the bonding force between the emulsified asphalt and the aggregate, increase the viscosity of the emulsified asphalt, make it easier to operate during the construction process, and help prevent stratification, thereby obtaining high-viscosity emulsified asphalt. The ternary polymer and nano-scale anhydrous calcium chloride act together as a dispersant, helping to evenly disperse the various components in the emulsified asphalt and improve the stability of the emulsion. The ternary polymer can also introduce special functional groups, thereby enhancing the elasticity, toughness and other mechanical properties of the asphalt, improving the aging resistance and extending the service life. By adjusting the ratio of each monomer in the AM-VP-VI ternary polymer, the hydrophilicity and hydrophobicity of the polymer can be controlled, thereby affecting the storage stability and construction performance of the emulsified asphalt.

[0027] Among them, the thickener is polyvinyl alcohol (PVA), polyacrylamide (PAM), cellulose derivatives such as hydroxypropyl methylcellulose (HPMC), etc. PVA has good water solubility and film-forming properties, and can enhance the mechanical stability and adhesion of emulsified asphalt. PAM is used to increase the viscosity of emulsified asphalt, improve its shear resistance and storage stability. Cellulose derivatives can increase the viscosity of the emulsion and improve its stability. In addition, antioxidants such as phenolic compounds can prevent emulsified asphalt from deteriorating due to oxidation during storage. Rust inhibitors such as sodium nitrite can prevent the inner wall of metal containers from rusting, thereby protecting the emulsified asphalt from contamination. Preservatives are sodium benzoate, potassium sorbate or isothiazolinone compounds, etc., which prevent the growth of microorganisms and the resulting corruption, stratification or performance degradation of emulsified asphalt.

[0028] Furthermore, the preparation method of the emulsified asphalt can be carried out according to the following steps:

[0029] (1) dispersing nanometer-scale anhydrous calcium chloride powder surface-modified with hexadecyltrimethoxysilane (CTMS) and AM-VP-VI ternary polymer emulsifier into water, adjusting the pH value to 2-3 with hydrochloric acid, and preheating to 60-70° C. to obtain an aqueous dispersion;

[0030] (2) heating the modified matrix asphalt to about 120-150° C. (e.g., 135° C.) until it is in a fluid state, ensuring good fluidity; while the aqueous dispersion is continuously stirred (500-1000 rpm), slowly pouring the molten modified matrix asphalt into the aqueous dispersion; gradually increasing the stirring speed during the process of pouring the modified matrix asphalt;

[0031] (3) Under the temperature condition of 80-90° C., use a colloid mill at a rotation speed of 3000-5000 rpm for 30-60 min until the mixture becomes uniform and has no obvious particles. Finally, adjust the pH value and add other additives (if any) as needed, stir evenly, and the emulsified asphalt is obtained.

[0032] In a fourth aspect, the present invention further provides a cold-mixed cold-paved emulsified asphalt concrete, which comprises, by mass percentage: 3-6% of the above-mentioned emulsified asphalt, 90-94% of aggregate and 0-3% of filler. The aggregate is crushed stone and sand of a certain grade, etc.; the filler is mineral powder (such as S95 mineral powder), and the mineral powder is selectively added as needed.

[0033] (III) Beneficial effects

[0034] The AM-VP-VI ternary polymer prepared by the present invention can be used to prepare high-viscosity and high-solid content emulsified asphalt with good storage stability, so that the solid content of the prepared emulsified asphalt is 70%-75% (the emulsified asphalt in the prior art generally does not exceed 70%, otherwise the stability is very poor), the 5d storage stability is less than 3%, and the average particle size of the asphalt particles is less than 3μm; the adhesion to the coarse aggregate is equivalent to that of hot-mix asphalt concrete, the asphalt softening point is ≥85°C, and the dynamic viscosity at 60°C is ≥23000Pa·s. The ternary polymer emulsifier of the present invention improves the high viscosity, high solid content and high storage stability of the emulsified asphalt as a whole.

[0035] By preparing emulsified asphalt with high viscosity and high solid content, and further using the emulsified asphalt with aggregates and fillers as a mixture, a cold-mixed and cold-laid emulsified asphalt concrete is obtained, which makes the cold-mixed and cold-laid emulsified asphalt concrete have a wider range of applications.

[0036] The present invention solves the technical problems in the prior art that emulsified asphalt has low viscosity and low solid content, and can usually only be used as a functional layer material in occasions such as penetration layer, adhesive layer, slurry seal layer, etc., but is difficult to be used as a cold-mixed and cold-laid asphalt concrete surface layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the infrared spectrum of the AM-VP-VI terpolymer prepared in Example 1.

[0038] Figure 2 This is the hydrogen nuclear magnetic resonance spectrum of the AM-VP-VI terpolymer prepared in Example 1.

[0039] Figure 3 TG-DSC analysis chart of the AM-VP-VI terpolymer prepared in Examples 1-4.

[0040] Figure 4 The bromophenol blue test results of the AM-VP-VI terpolymer prepared in Example 1 are shown. DETAILED DESCRIPTION

[0041] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.

[0042] Example 1

[0043] This embodiment provides an AM-VP-VI ternary polymer emulsifier, and the preparation method is as follows:

[0044] (1) Weigh 2.6655 g of acrylamide, 2.50065 g of N-vinylpyrrolidone, and 1.41165 g of N-vinylimidazole and dissolve them in 50 mL of deionized water to obtain a mixed solution with a total concentration of 1.5 mol / L. Then, nitrogen gas was introduced into the mixed solution for 30 min to remove dissolved oxygen in the mixed solution.

[0045] (2) The mixed solution was heated to 50°C, and 0.052 mol / L azobisisobutylamidine hydrochloride initiator (aqueous solution) was added to the mixed solution at a rate of 30 mL / h under a nitrogen atmosphere, and the reaction temperature was controlled to be 48-50°C, the stirring speed was 190 rpm, and the reaction was carried out for 8 hours. Finally, acetone was added in an amount of 2 times the volume of the reaction system, stirred, precipitated, separated, washed with water once, washed with ethanol once, and dried in a vacuum drying oven at 50°C for 24 hours to obtain an AM-VP-VI ternary polymer emulsifier; wherein the molar ratio of the three monomers of AM, NVP and NVI was 5:3:2.

[0046] Example 2

[0047] This embodiment provides an AM-VP-VI ternary polymer emulsifier, and the preparation method is as follows:

[0048] (1) Weigh 2.8432 g of acrylamide, 3.3342 g of N-vinylpyrrolidone, and 2.8233 g of N-vinylimidazole and dissolve them in 50 mL of deionized water. Then, introduce nitrogen gas for 35 min to remove dissolved oxygen in the mixed solution.

[0049] (2) The mixed solution was heated to 52°C, and 0.050 mol / L azobisisobutylamidine hydrochloride initiator (aqueous solution) was added to the mixed solution at a rate of 36.25 mL / h under a nitrogen atmosphere, and the reaction temperature was controlled to be 50-52°C, the stirring speed was 200 rpm, and the reaction was carried out for 8 hours. Finally, acetone was added in an amount of 2 times the volume of the reaction system, stirred, precipitated, separated, washed with ethanol twice, and dried in a vacuum drying oven at 50°C for 24 hours to obtain an AM-VP-VI ternary polymer emulsifier; wherein the molar ratio of the three monomers of AM, NVP and NVI was 4:3:3.

[0050] Example 3

[0051] This embodiment provides an AM-VP-VI ternary polymer emulsifier, and the preparation method is as follows:

[0052] (1) Weigh 2.1324 g of acrylamide, 3.3342 g of N-vinylpyrrolidone, and 1.8822 g of N-vinylimidazole and dissolve them in 50 mL of deionized water. Then, introduce nitrogen gas for 30 min to remove dissolved oxygen in the mixed solution.

[0053] (2) The mixed solution was heated to 49°C, and 0.042 mol / L azobiscyanovaleric acid ACVA (aqueous solution) was added to the mixed solution at a rate of 31.25 mL / h under a nitrogen atmosphere, and the reaction temperature was controlled to be 48-49°C, the stirring speed was 220 rpm, and the reaction was carried out for 8 hours. Finally, acetone was added in an amount of 2 times the volume of the reaction system, stirred, precipitated, separated, washed with ethanol twice, and dried in a vacuum drying oven at 50°C for 24 hours to obtain an AM-VP-VI ternary polymer emulsifier; wherein the molar ratio of the three monomers AM, NVP and NVI was 3:3:2.

[0054] Example 4

[0055] This embodiment provides an AM-VP-VI ternary polymer emulsifier, and the preparation method is similar to that of Example 1, except that the masses of the three polymerization monomers of acrylamide, N-vinyl pyrrolidone and N-vinylimidazole in Example 1 are adjusted to: weigh 1.4216g acrylamide, 3.3342g N-vinyl pyrrolidone and 4.7055g N-vinylimidazole. The remaining steps refer to Example 1. In the AM-VP-VI ternary polymer emulsifier prepared in this embodiment, the molar ratio of the three monomers of AM, NVP and NVI is 2:3:5.

[0056] like Figure 1 The infrared spectrum of the AM-VP-VI terpolymer prepared in Example 1 is shown in FIG. -1 The double peaks corresponding to primary amides include 3340 cm -1 NH asymmetric stretch, 3194cm -1 NH symmetric stretching. 3000-2900cm -1 Corresponding to CH vibration in the polymer main chain. -1 (-CONH2)C=O stretching can be observed at 1665cm -1 The stretching vibration of the carbonyl group (C=O) in the lactam ring of N-vinyl pyrrolidone is nearly overlapped, and as the amount of acrylamide monomer decreases, the characteristic peak tends to weaken. -1 The CN stretching of acrylamide is corresponding to the CN stretching of acrylamide. -1 The characteristic ring bending and ring stretching band infrared peaks of imidazole were observed to gradually increase at 1230cm -1 The imidazole ring is CN stretching, 1110 and 1084 cm -1 The stretching vibration of the CH of the imidazole ring can be observed.

[0057] like Figure 2The following is the nuclear magnetic resonance hydrogen spectrum of the AM-VP-VI terpolymer prepared in Example 1. The AM-VP-VI terpolymer was dissolved in D2O. 1 The H-NMR spectrum shows that δ = 4.790 ppm is the chemical shift of the solvent heavy water; the chemical shifts of hydrogen in the main chain methyl (-CH3-) and methylene (-CH2-) are mainly concentrated in 1.24-1.85 ppm; δ = 2.36 ppm is the chemical shift of acrylamide -CH-; δ = 2.20 ppm (2H), 1.97 ppm (2H), 3.26 ppm (2H) are the chemical shifts of hydrogen on the methylene group of the pyrrolidone ring. In addition, in the terpolymer 1 In the H-NMR spectrum, the characteristic peak of 6.7-8.0 ppm is attributed to the hydrogen atom on the imidazole ring in N-vinyl imidazole. Combined with infrared spectroscopy, it is confirmed that acrylamide, N-vinyl imidazole and N-vinyl pyrrolidone are successfully synthesized as a cationic terpolymer emulsifier by aqueous solution method.

[0058] like Figure 3 As shown, the TG-DSC analysis diagram of the AM-VP-VI ternary polymer prepared in Examples 1-4. The thermal decomposition process of the polymers synthesized with different monomer ratios can be roughly divided into three stages. In the first stage (140°C-320°C), due to the residual solvent in the polymer, the mass loss is mainly due to the evaporation of water adsorbed by the polymer and the volatilization of free water, and the mass loss is approximately in the range of 10%-15%. In the second stage (320°C-450°C), the functional groups such as amide and imidazole five-membered heterocyclic ring in the corresponding copolymer undergo thermal decomposition, so that the grafted side chemical groups are separated from the polymer main chain. In the third stage (450°C-800°C), the decomposition of the CC bond of the polymer main chain and the pyrrolidone ring that has not been completely decomposed in the side chain leads to further degradation of the polymer.

[0059] like Figure 4 The figure shows the bromophenol blue test of the AM-VP-VI terpolymer prepared in Example 1. Take 10 ml of the prepared bromophenol blue solution in a test tube bottle, add 2 ml of a 1.0% cationic surfactant aqueous solution, shake the push-type bottle, and observe that the bromophenol blue solution changes from red to blue-purple. This is because the bromophenol blue reagent complexes with cationic substances, causing the color to change from red to blue-purple, which indicates that the AM-VP-VI terpolymer is a cationic emulsifier.

[0060] Comparative Example 1

[0061] In this comparative example, based on Example 1, the amounts of N-vinyl pyrrolidone and N-vinylimidazole were increased, but the monomer acrylamide was not added, that is, 3.750 g of N-vinyl pyrrolidone and 2.1175 g of N-vinylimidazole were weighed and dissolved in 50 mL of deionized water, and a cationic binary polymer was prepared according to the method of Example 1, wherein the molar ratio of N-vinyl pyrrolidone to N-vinylimidazole was 3:2.

[0062] Comparative Example 2

[0063] In this comparative example, based on Example 1, the amounts of acrylamide and N-vinylimidazole were increased, but the monomer N-vinylpyrrolidone was not added, that is, 3.998 g of acrylamide and 2.1175 g of N-vinylimidazole were weighed and dissolved in 50 mL of deionized water, and a cationic binary polymer was prepared according to the method of Example 1, wherein the molar ratio of acrylamide to N-vinylimidazole was 5:2.

[0064] Example 5

[0065] In this example, the AM-VP-VI ternary polymer emulsifier prepared in Example 1 is used to prepare modified emulsified asphalt. The composition and preparation method of the modified emulsified asphalt are as follows:

[0066] (1) Preparation of modified base asphalt

[0067] The 70# matrix asphalt (grade Zhonghai-90) is melted under heating conditions, SBS and SBR are dispersed in the matrix asphalt, and a shearing machine is used to treat it at 12000rpm for 5 minutes to obtain a modified matrix asphalt; SBS accounts for 4% of the original matrix asphalt mass, and SBR accounts for 3% of the original matrix asphalt mass.

[0068] (2) Preparation of emulsified asphalt

[0069] The raw materials were weighed according to 75% of modified base asphalt, 1% of AM-VP-VI ternary polymer emulsifier prepared in Example 1, 0.3% of hexadecyltrimethoxysilane (CTMS) modified nano anhydrous calcium chloride powder (particle size 20-50nm), 0.1% of hydrochloric acid (pH regulator), 0.5% of HPMC (thickener), 0.1% of sodium benzoate (preservative), 0.2% of butylated hydroxyanisole BHA (antioxidant), and the balance was deionized water, and emulsified asphalt was prepared according to the following method:

[0070] Disperse nanometer-scale anhydrous calcium chloride powder surface-modified with hexadecyltrimethoxysilane (CTMS) and AM-VP-VI ternary polymer emulsifier into water, adjust the pH value to 2-3 with hydrochloric acid, and preheat to 70°C to obtain an aqueous dispersion; heat the modified matrix asphalt to about 135°C and heat it to a flowing state to ensure good fluidity; slowly pour the molten modified matrix asphalt and thickener into the aqueous dispersion while constantly stirring the aqueous dispersion (500rpm); gradually increase the stirring speed to 1000rpm during the process of pouring the asphalt; then, use a high-speed shearing machine at 85°C at 4500rpm to shear the mixture for 45 minutes until the mixture becomes uniform and has no obvious particles; finally, adjust the pH value to 2-3 as needed, add additives such as preservatives and antioxidants, and stir evenly to obtain emulsified asphalt.

[0071] Example 6

[0072] In this example, the AM-VP-VI ternary polymer emulsifier prepared in Example 1 is used to prepare modified emulsified asphalt. The composition and preparation method of the modified emulsified asphalt are as follows:

[0073] (1) Preparation of modified base asphalt

[0074] The 70# matrix asphalt (grade Zhonghai-90) is melted under heating conditions, SBS and SBR are dispersed in the matrix asphalt, and a shearing machine is used to treat it at 12000rpm for 5 minutes to obtain a modified matrix asphalt; SBS accounts for 5% of the original matrix asphalt mass, and SBR accounts for 4% of the original matrix asphalt mass.

[0075] (2) Preparation of emulsified asphalt

[0076] Each raw material is weighed according to 74% of modified base asphalt, 1.2% of AM-VP-VI ternary polymer emulsifier prepared in Example 2, 0.4% of hexadecyltrimethoxysilane (CTMS) modified nano anhydrous calcium chloride powder (particle size 20-50nm), 0.15% of hydrochloric acid (pH adjuster), 0.1% of sodium benzoate (preservative), 0.1% of rust inhibitor, 0.15% of butylated hydroxyanisole BHA (antioxidant), and the remainder is deionized water, and emulsified asphalt is prepared according to the method of Example 5.

[0077] Referring to the Technical Specification for Preventive Maintenance of Highway Asphalt Pavement (JTGT5142-01-2021), the properties of the above modified emulsified asphalt were tested and the test results were recorded in the following table:

[0078]

[0079] The solid content of the modified emulsified asphalt prepared in Example 5-6 reaches 74-75%, and the storage stability (%) of this high-solid content emulsified asphalt can fully meet the technical indicators. At present, the highest existing emulsified asphalt is only 63%, and rarely can reach 70%; the optimal 5d storage stability of the prior art emulsified asphalt is ≤5%, while the 5d storage stability of the modified emulsified asphalt prepared in Example 5-6 can reach <3%. The average particle size of the asphalt particles in the prior art emulsified asphalt is <5μm, and the average particle size of the asphalt particles in the modified emulsified asphalt prepared in Example 5-6 is <3μm. In addition, the softening point of the modified emulsified asphalt prepared in Example 5-6 is ≥82°C, and the softening point of the emulsified asphalt in the prior art is generally ≥75°C. Therefore, the modified emulsified asphalt prepared by the present invention has better high temperature working performance and can adapt to high temperature climate environment.

[0080] Further test results also show that the 60°C dynamic viscosity of the modified emulsified asphalt prepared in Examples 5-6 is ≥23000Pa.s, and the 60°C dynamic viscosity of the emulsified asphalt in the prior art is ≥20000Pa.s. The greater the dynamic viscosity, the stronger the bonding force between the emulsified asphalt and the aggregate, and the more effectively it can improve the strength and durability of the final road surface, making it more suitable for use as an asphalt concrete surface layer. In addition, the high viscosity gives the emulsified asphalt better storage stability and is not easy to delaminate or demulsify. Further, the modified emulsified asphalt prepared in this example was tested for adhesion to coarse aggregate, and the results showed that the adhesion performance of the emulsified asphalt to coarse aggregate is comparable to that of ordinary hot-mix asphalt to coarse aggregate.

[0081] When the AM-VP-VI ternary polymer emulsifier in Example 5 is replaced by the cationic binary polymer emulsifier in Comparative Example 1-2 in equal amounts, the obtained modified emulsified asphalt has a weaker adhesion to coarse aggregate, a poorer uniformity in mixing with coarse and fine aggregates, and a decreasing storage stability, compared with the modified emulsified asphalt in Example 5, and its 5d storage stability (%) is about 4.6-4.7%. This shows that although Comparative Example 1-2 can also provide a cationic macromolecular polymer emulsifier, the binary polymer emulsifier prepared in Comparative Example 1-2 does not improve the stability of the modified emulsified asphalt with a high solid content as compared with the embodiments of the present invention, and the adhesion of the modified emulsified asphalt also has a decreasing trend, all of which are not conducive to the use of emulsified asphalt in cold-mixed and cold-laid asphalt concrete surface layers.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A polymer emulsifier for cold mix cold paving emulsified asphalt concrete, characterized in that: The polymer emulsifier is a terpolymer generated by polymerization of acrylamide AM, N-vinyl pyrrolidone NVP and N-vinyl imidazole NVI, and has a molecular weight of 3000-10000; wherein the molar ratio of the three monomers of AM, NVP and NVI is 5-2:3:2-5.

2. A method for preparing a polymer emulsifier for cold mix cold paving emulsified asphalt concrete according to claim 1, characterized in that: The steps include: S1, dispersing acrylamide monomer AM, N-vinyl pyrrolidone monomer NVP and N-vinyl imidazole monomer NVI in water to obtain a mixed solution; S2, treating the mixed solution to remove or reduce dissolved oxygen in the mixed solution; S3. Under the protection of inert gas, add a water-soluble initiator to the mixed solution, control the reaction temperature to ≤53°C to carry out polymerization reaction, and keep stirring during the polymerization process; S4. After the reaction is completed, acetone is added to the reaction system for precipitation, the precipitate is washed, and dried in a vacuum drying oven to obtain an AM-VP-VI ternary polymer emulsifier.

3. The method for preparing a polymer emulsifier according to claim 2, wherein in S1, the molar ratio of the three monomers AM, NVP and NVI is 5-2:3:2-5.

4. The method for preparing a polymer emulsifier according to claim 2, wherein in S1, the total molar concentration of the three monomers in the mixed solution is 1.2-1.8 mol / L.

5. The method for preparing a polymer emulsifier according to claim 2, wherein in S2, nitrogen is introduced into the mixed solution to remove or reduce dissolved oxygen in the mixed solution; specifically, nitrogen is continuously introduced into the mixed solution for 30-50 minutes.

6. The method for preparing a polymer emulsifier according to claim 2, wherein in S3, the water-soluble initiator is azobisisobutylamidine hydrochloride; the azobisisobutylamidine hydrochloride is added in the form of a low-concentration solution at a uniform flow rate during the polymerization reaction, and the reaction temperature is controlled at 50°C.

7. The method for preparing a polymer emulsifier according to claim 6, wherein in S3, the concentration of azobisisobutylamidine hydrochloride solution is 0.05-0.06 mol / L, and the total amount of azobisisobutylamidine hydrochloride is 1 / 6-1 / 8 of the total molar ratio of the reaction monomers; in S3, the stirring speed during the polymerization process is 180 rpm-220 rpm; and the reaction time is 7.5-8.5 h.

8. The method for preparing a polymer emulsifier according to claim 2, wherein in S4, after the reaction is completed, 1.5-3 times the volume of acetone of the reaction system is added to the reaction system, the mixture is stirred and allowed to stand, the precipitate is separated, and the precipitate is washed with ethanol for 2-3 times; and the mixture is dried in a vacuum drying oven at 50° C. for 24 hours to obtain an AM-VP-VI ternary polymer emulsifier.

9. An emulsified asphalt, characterized in that: Measured by mass percentage, it comprises: 70-75% of modified base asphalt, 0.5-1.2% of the AM-VP-VI ternary polymer emulsifier described in claim 1, 0.1-0.5% of a solid nano-powder stabilizer, 0.1-1% of an auxiliary agent and the remainder of water; the auxiliary agent comprises a pH regulator, which adjusts the pH of the emulsified asphalt to 2-3; the solid nano-powder stabilizer is a nano-scale anhydrous calcium chloride powder; the modified base asphalt is a base asphalt co-modified by SBS and SBR.

10. A cold mix cold paving emulsified asphalt concrete, characterized in that: Calculated by mass percentage, it comprises: 3-6% of the emulsified asphalt according to claim 9, 90-94% of aggregate and 0-3% of filler.

Citation Information

Patent Citations

  • Composition of cationic asphalt emulsifier, preparation method and application thereof

    CN101845228A

  • Styling agents having maximum hold

    CN103596549A

  • Anti-high temperature filtrate reducer latex for drilling fluid and production technology of anti-high temperature filtrate reducer latex

    CN106978153A

  • SBR modified emulsified asphalt and preparation method thereof

    CN109929258A

  • Polymer asphalt emulsifier as well as preparation method and application thereof

    CN112920311A